Analisis penggunaan antidiabetik dan antihipertensi pada pasien diabetes komorbid hipertensi di Puskesmas Mrebet - Melani, Reina; Kurniasih, Khamdiyah Indah; Fauziah, Fauziah (Journal of Pharmaceutical and Sciences, 2023)
Diabetes Mellitus (DM) is a chronic disease characterised by high blood sugar levels. Diabetes mellitus is considered the "mother disease" because it is the mother of various diseases such as hypertension, heart disease, stroke, kidney failure and blindness. There were 13,117 DM cases in Purbalingga Regency, and 14,035 people were provided services according to procedures. Increased blood glucose levels (hyperglycemia) cause intravascular fluid resistance, which results in an increase in body fluid volume and an increase in peripheral arterial resistance. These two conditions are the basis for hypertension. There is a need for appropriate antidiabetic therapy to treat hypertension comorbid DM disorders. This research was conducted at the Mrebet Community Health Center, Purbalingga Regency, where the results obtained were 55 data on the use of prolanis medication for DM comorbid hypertension patients. In this study, the most common single therapy was metformin (12.7%), then the two most common combinations were glimepiride and acarbose (41.8%), while the three combinations used were metformin, glimepiride and acarbose (12.7%). The most common single antihypertensive was Lisinopril (28.2%), and the most common combination was Lisinopril + Amlodipine (28.2%).